Distinct Roles of CK2- and AKT-Mediated NF-κB Phosphorylations in Clasmatodendrosis (Autophagic Astroglial Death) within the Hippocampus of Chronic Epilepsy Rats - Ji-Eun Kim; Duk-Shin Lee; Tae-Hyun Kim; Hana Park; Tae-Cheon Kang (MDPI AG, 2023)
The downregulation of glutathione peroxidase-1 (GPx1) plays a role in clasmatodendrosis (an autophagic astroglial death) in the hippocampus of chronic epilepsy rats. Furthermore, N-acetylcysteine (NAC, a GSH precursor) restores GPx1 expression in clasmatodendritic astrocytes and alleviates this autophagic astroglial death, independent of nuclear factor erythroid-2-related factor 2 (Nrf2) activity. However, the regulatory signal pathways of these phenomena have not been fully explored. In the present study, NAC attenuated clasmatodendrosis by alleviating GPx1 downregulation, casein kinase 2 (CK2)-mediated nuclear factor-κB (NF-κB) serine (S) 529 and AKT-mediated NF-κB S536 phosphorylations. 2-[4,5,6,7-Tetrabromo-2-(dimethylamino)-1H-benzo[d]imidazole-1-yl]acetic acid (TMCB; a selective CK2 inhibitor) relieved clasmatodendritic degeneration and GPx1 downregulation concomitant with the decreased NF-κB S529 and AKT S473 phosphorylations. In contrast, AKT inhibition by 3-chloroacetyl-indole (3CAI) ameliorated clasmatodendrosis and NF-κB S536 phosphorylation, while it did not affect GPx1 downregulation and CK2 tyrosine (Y) 255 and NF-κB S529 phosphorylations. Therefore, these findings suggest that seizure-induced oxidative stress may diminish GPx1 expression by increasing CK2-mediated NF-κB S529 phosphorylation, which would subsequently enhance AKT-mediated NF-κB S536 phosphorylation leading to autophagic astroglial degeneration.